An MRI study on the relations between muscle atrophy, shoulder function and glenohumeral deformity in shoulders of children with obstetric brachial plexus injury - van Gelein Vitringa, Valerie M; van Kooten, Ed O; Mullender, Margriet G; van Doorn-Loogman, Mirjam H; van der Sluijs, Johannes A (Journal of Brachial Plexus and Peripheral Nerve Injury, 2009)
Background A substantial number of children with an obstetric brachial plexus lesion (OBPL) will develop internal rotation adduction contractures of the shoulder, posterior humeral head subluxations and glenohumeral deformities. Their active shoulder function is generally limited and a recent study showed that their shoulder muscles were atrophic. This study focuses on the role of shoulder muscles in glenohumeral deformation and function.Methods This is a prospective study on 24 children with unilateral OBPL, who had internal rotation contractures of the shoulder (mean age 3.3 years, range 14.7 months to 7.3 years). Using MR imaging from both shoulders the following parameters were assessed: glenoid form, glenoscapular angle, subluxation of the humeral head, thickness and segmental volume of the subscapularis, infraspinatus and deltoid muscles. Shoulder function was assessed measuring passive external rotation of the shoulder and using the Mallet score for active function. Statistical tests used are t-tests, Spearman’s rho, Pearsons r and logistic regression.Results The affected shoulders showed significantly reduced muscle sizes, increased glenoid retroversion and posterior subluxation. Mean muscle size compared to the normal side was: subscapularis 51%, infraspinatus 61% and deltoid 76%. Glenoid form was related to infraspinatus muscle atrophy. Subluxation was related to both infraspinatus and subscapularis atrophy. There was no relation between atrophy of muscles and passive external rotation. Muscle atrophy was not related to the Mallet score or its dimensions.Conclusion Muscle atrophy was more severe in the subscapularis muscle than in infraspinatus and deltoid. As the muscle ratios are not related to passive external rotation nor to active function of the shoulder, there must be other muscle properties influencing shoulder function.